2013
DOI: 10.1021/cb400755b
|View full text |Cite
|
Sign up to set email alerts
|

General Method for Regulating Protein Stability with Light

Abstract: Posttranslational regulation of protein abundance in cells is a powerful tool for studying protein function. We here describe a novel genetically encoded protein domain that is degraded upon exposure to non-toxic blue light. We demonstrate that fusion proteins containing this domain are rapidly degraded in cultured cells and in zebrafish upon illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 20 publications
2
141
0
2
Order By: Relevance
“…Three are based on photosensitive plant proteins (cryptochromes 911 , light-oxygen-voltage (LOV) domains 1215 and phytochromes 1618 ), and one is based on the fluorescent protein Dronpa 19 , which was isolated from the coral Pectiniidae 20 . Other recent publications discuss the use of optogenetic proteins that manipulate specific signalling events, such as those that regulate neuronal excitability 4,21 , cyclic nucleotides 22,23 and heterotrimeric G protein signalling 24,25 , or proteins that are irreversibly activated 2628 or inactivated 29 by light.…”
Section: Overview Of Optogenetic Systemsmentioning
confidence: 99%
“…Three are based on photosensitive plant proteins (cryptochromes 911 , light-oxygen-voltage (LOV) domains 1215 and phytochromes 1618 ), and one is based on the fluorescent protein Dronpa 19 , which was isolated from the coral Pectiniidae 20 . Other recent publications discuss the use of optogenetic proteins that manipulate specific signalling events, such as those that regulate neuronal excitability 4,21 , cyclic nucleotides 22,23 and heterotrimeric G protein signalling 24,25 , or proteins that are irreversibly activated 2628 or inactivated 29 by light.…”
Section: Overview Of Optogenetic Systemsmentioning
confidence: 99%
“…This toolbox now offers the possibility to photocontrol a variety of cellular protein functions from chromatin modification to DNA transcription [20][21][22][23][24][25][26] or recombination 23 , protein translocation 19,22,27,28 , enzymatic activity [29][30][31] , cell morphology 22,32 , signaling pathways 7,27,30,31 and protein degradation 33,34 (Table 1). Recent works have focused on improving the response timescale and the signal-to-noise ratio and have expanded the spectrum of available wavelengths ( Table 1), making multiplexing possible (Box 1 and Fig.…”
Section: Genetically Encodable Photoactuatorsmentioning
confidence: 99%
“…While we already observed strong inhibition of reporter expression from the VP16-and VP64-based systems when Med25VBD was transfected in equal amounts to the other components (10-fold and 20-fold respectively), the p65-based system was barely repressed 2-fold at a 5-fold Having confirmed that Med25VBD can be used to potently and selectively repress VP64-dependent transgene expression, we embarked upon the engineering of a light-controlled VP64 inhibitor. To this end, we turned to the recently-published B-LID (blue light-inducible degradation) domain (Bonger et al 2014). This optogenetic protein degradation tool is based on the LOV2 domain from Avena sativa phototropin 1 that has been modified by adding an RRRG-degradation signal to its J-helix.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%